Knowledge, attitude and practice towards zero carbon buildings: Hong Kong case. (20th November 2020) - Pan, Mi; Pan, Wei
Abstract: The 'zero carbon building (ZCB)' approach has been hailed as an innovative strategy for addressing climate change and achieving a low carbon society. There has been burgeoning research on the technical aspects of ZCBs. However, the aspect of stakeholder engagement, albeit imperative for zero carbon development, has been largely overlooked in the literature. This paper examines stakeholder knowledge, attitude and practice (KAP) with regard to ZCBs in a systems manner, employing a new KAP model that integrates ontology, axiology and epistemology as the theoretical lens. The research was carried out through a questionnaire survey and focus group discussions with multiple stakeholders in the building industry in Hong Kong, which is a typical example of a high-density city. The results indicate the generally ambiguous and inconsistent knowledge, relatively negative attitude, and poor practice of stakeholders towards ZCBs. The statistical analysis findings reveal that differentiation exists between different stakeholder groups as to their knowledge, and this highlights the significant role that explicit ZCB knowledge plays in creating a knowledge-induced attitude that favours changes in practice leading to zero carbon developments. The applicability of the developed KAP model is verified using the case of Hong Kong, enabling the dialectics and complexities of stakeholder KAP towards ZCBs to be further clarified. Practical implications are provided to enhance the knowledge, shape the attitudes, and encourage the practices of building towards zero carbon in future cities. Highlights: Knowledge, attitude and practice (KAP) with regard to ZCB are systematically examined. A KAP model that integrates ontology, axiology and epistemology of ZCB is developed. There are gaps between practitioners and researchers regarding knowledge of ZCB. Stakeholders in HK have relatively negative attitude and poor practice towards ZCB. Well-structured knowledge is key to induce attitude and practice favoring ZCB.